The Effect Of Leaflet Compared To Power Point On Knowledge And Attitude Of Pregnant Mothers About Hepatitis B In UPTD Puskesmas Kedokan Bunder, Indramayu Regency In 2020 - Lisnawati .; Sri Hani Purwati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2021)
Introduction: Every year Hepatitis B has experienced a very rapid increase from <1% up to now reaching 5%, it is estimated that worldwide has a history of Hepatitis B and has Hepatitis B up to 2 billion people. Pregnant women have a high risk of transmitting infections around 1.5 to 2.5% of pregnant women worldwide who have Hepatitis B. Areas with the highest risk include the Mediterranean, Middle East (Gulf countries, Saudi Arabia and Turkey), Pakistan, Central, and North Asia namely Japan, Taiwan, Greenland and Africa, the Amazon basin and certain regions of the Indonesia Pacific. This study aims to determine the effect of leaflets versus power points on the knowledge and attitudes of pregnant women about Hepatitis B. Methods: analytical research with Quasi-experiment technique with pretest and posttest Two Group Design designs taken with accidental sampling technique obtained a sample of 20 people in the leaflet group and 20 people in the powerpoint group. The instrument used was a questionnaire created by researchers who had tested the validity and reliability. The analysis used in the knowledge variable uses the Wilcoxon test and in the attitude, variable use the Mcnemar test. To know the comparison of knowledge using the Independent t-test and the attitude using the Chi-square test. Results: the results of the independent t-test were used to find out the comparison between the leaflet group and the PowerPoint group, the p-value was 0.206, and the chi-square test between the leaflet group and the PowerPoint group obtained a p-value of 1,000. Conclusion: there was no difference in the effect of using leaflets compared to power points on the knowledge and attitudes of pregnant women about Hepatitis B in UPTD Puskesmas Kedokan Bunder Indramayu Regency in 2020.